Smart Computing and Informatics Proceedings of the First International Conference on SCI 2016, Volume 2 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Das, Swagatam; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This volume contains 68 papers presented at SCI 2016: First International Conference on Smart Computing and Informatics. The conference was held during 3-4 March 2017, Visakhapatnam, India and organized communally by ANITS, Visakhapatnam and supported technically by CSI Division V - Education and Research and PRF, Vizag. This volume contains papers mainly focused on smart computing for cloud storage, data mining and software analysis, and image processing.
Preface -- About the editors -- Conference Organizing Committee -- Table of Contents -- 68 Chapters -- Author Index.
Keywords: Telecommunication; Quantitative research; Artificial intelligence; Communications Engineering, Networks; Data Analysis and Big Data; Artificial Intelligence